EKSPERIMENTASI MODEL PEMBELAJARAN COOPERATIVE SCRIPT PADA PEMBELAJARAN MATEMATIKA - Robia Astuti; Nurmitasari Nurmitasari; Susanti Diah Lestari (Universitas Muhammadiyah Kotabumi, 2017)
The aimed of this research was: 1) to know the difference of the average of mathematics learning result of students obtained through Cooperative Script model with the average of student learning result obtained through STAD type cooperative learning model in class VII class material in SMP Negeri 1 Banyumas, and 2) to know the average of mathematics learning outcomes which is better between students whose learning is obtained through Cooperative Script model with students whose learning is obtained through STAD type cooperative learning model in class VII class material in SMP Negeri 1 Banyumas. The population in this study is all students of class VII even semester SMP Negeri 1 Banyumas academic year 2016-2017 with the number of 162 students divided into 5 (five) class. The sampling technique uses cluster random sampling. Obtained Class VII A amounted to 33 students as experimental class and class VII B which amounted to 33 students as a control class. Learning outcomes obtained through the test in the form of a description consists of 4 items. Data were analyzed using two-t test and one-party test. Data analysis using two-party t test with 5% real level obtained by result of 1,999 and 2,602, < , so reject H0 and accept H1 which indicate that there is difference of mean result of learning of mathematics between them. Analysis of data using t-test one party with 5% real level obtained ttable = 1.670 and tcount = 2.602 turns < , so H0 rejected and accepted H1 which indicates that the average mathematics learning outcomes of students applied Cooperative Script learning model more both from the STAD type cooperative learning model. The result of t test analysis concluded that there is influence of Cooperative Script model to the result of learning of class VII in SMP Negeri 1 Banyumas